HLA-DQ Specific Alloantibodies Modify Allogenic Endothelial Cell Immunogenicity and Impair the Expansion of Anti-Inflammatory FoxP3 High Regulatory T Lymphocytes. (July 2018) - Cross, Amy; Lion, Julien; Taupin, Jean-Luc; Poussin, Karine; Glotz, Denis; Mooney, Nuala
Abstract : Recent clinical studies have highlighted the prevalence of de novo circulating Donor-Specific Antibodies (DSA) against HLA-DQ following solid organ transplantation. The emergence of HLA-DQ DSA has been associated with poor graft outcome. The allograft microvascular endothelium is known to upregulate HLA-DQ expression during rejection. The allograft endothelium is directly exposed to circulating anti-donor antibodies and as a result, becomes a principal site of DSA binding and thereby the target of antibody-mediated damage. Endothelial activation is a feature of antibody-mediated rejection and is reported to arise from inflammation, DSA binding and complement activation. Activated endothelial cells modulate the recipient's immune response as a result of their interactions with CD4+ T lymphocytes. Plasmapheresis samples were obtained from alloimmunized patients with high levels of circulating DSA. Antibodies were isolated using protein G beads, and their HLA specificity was assessed by Luminex. Antibodies were evaluated for binding to microvascular endothelial cells, and a time course of binding was established by flow cytometry. Patient antibodies specific for relevant HLA-DQ alleles were used to assess potential signal transduction from antibody-binding to endothelial cells. HLA-DQ DSA induced transient phosphorylation of Akt and S6 Kinase. This was confirmed using a monoclonal anti-HLA DQ antibody. Alloantibodies against HLA-DQ alleles not expressed by our cell model did not induce specific signalling events. Previously, we found that HLA-DR+ endothelial cells are capable of inducing alloproliferation of CD4+ T lymphocytes and selectively expanding Th17 and FoxP3 high T regulatory cell (Treg) subsets (Taflin PNAS 2011, Lion Am J Transplant 2016). The presence of intragraft Th17 correlates with shorter graft survival, whilst the proportion of Treg cells has been implicated in tolerance. To assess the functional consequences of DSA binding, endothelial cells were stimulated with HLA-DQ DSA for one hour preceding co-culture with allogenic peripheral blood mononuclear cells. After seven days, CD4+ T cell subsets were analysed by intracellular cytokine staining. HLA-DQ DSA modified endothelial cell immunogenicity, resulting in a reduction in alloproliferation and in Treg expansion. Alloantibodies against HLA-DQ alleles not expressed by our cell model did not alter alloproliferation or Treg expansion. The impaired amplification of anti-inflammatory Treg cells, in combination with an unaltered expansion of the Th17 subset, leads to an overall pro-inflammatory orientation of alloreactive CD4+ T cells. This altered composition of CD4+ T cells, due to HLA-DQ binding to endothelial cells, may exacerbate allograft damage and reduce allograft tolerance. AC was supported by the Société Francophone de Transplantation (SFT) .